2020
DOI: 10.1155/2020/6707012
|View full text |Cite
|
Sign up to set email alerts
|

An Effective and Simple Way to Establish Elastase-Induced Middle Carotid Artery Fusiform Aneurysms in Rabbits

Abstract: Objective. Elastase-induced aneurysms in rabbits have been proposed as a preclinical tool for device development, but there is still much deficiency in those aneurismal models. So we need to explore the efficient and convenient animal models for the investigation of intracranial aneurysms. Then, we compared and analyzed three methods of elastase-induced carotid artery aneurysms in rabbits and aimed to find a simple, effective, and reproducible method for creating elastase-induced aneurysms. Methods. 42 standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In 1993, Hashimoto [ 31 ] used this modality to measure blood flow velocity in a rabbit venous pouch IA model. Since then, this technique has been used in a number of IA studies to study blood flow velocity in cerebral arteries or within the IA and to check IA patency over time or after treatments [ 41 , 42 , 44 , 91 , 154 , 176 , 178 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993, Hashimoto [ 31 ] used this modality to measure blood flow velocity in a rabbit venous pouch IA model. Since then, this technique has been used in a number of IA studies to study blood flow velocity in cerebral arteries or within the IA and to check IA patency over time or after treatments [ 41 , 42 , 44 , 91 , 154 , 176 , 178 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 173 ] 2019 X Surgical Dogs Saccular X X X Rajabzadeh-Oghaz H. [ 174 ] 2019 X Endogenous Mice Saccular X Wanderer S. [ 175 ] 2020 X Surgical Rabbits Saccular X X Lyu Y. [ 176 ] 2020 X Surgical Rabbits Fusiform X X Fries F. [ 177 ] 2020 X Surgical Rabbits Saccular X …”
Section: Methodsmentioning
confidence: 99%
“…The copy number of hsa-miR-3907 was higher in autosomal dominant polycystic kidney disease patients with hypertension than in autosomal dominant polycystic kidney disease patients without hypertension [40]. Previous studies have shown that the CD34 molecule (CD34) is an important regulator of chronic inflammatory vascular disease, and its levels are abnormal in aneurysms [41]. In the present study, MFAP4 and CD34 were the target DEmRNAs of hsa-miR-4793-3p and hsa-miR-3907, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 studies managed to follow aneurysmal remodeling in mice over 3 months using really high-field MRI (9,4T) ( 100 , 101 ). Regarding IA's hemodynamics, Doppler ultrasound imaging can be used to measure blood flow velocity in rabbit models of internal carotid aneurysm ( 99 , 102 , 103 ).…”
Section: Inflammation Imagingmentioning
confidence: 99%